1996
DOI: 10.1016/0014-5793(96)00109-3
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosinase and related proteins in mammalian pigmentation

Abstract: Tyrosinase is the key enzyme in pigment synthesis, initiating a cascade of reactions which convert the amino acid tyrosine to the melanin biopolymer. Two other tyrosinase-related proteins (TRP) are known, TRP-1 (probably DHICAoxidase) and TRP-2 (DOPAchrome tautomerase). These proteins show about 40% homology, and recent results have indicated that the genes might be derived from a common ancestor. We will discuss recent findings on genomic organization, and on the proteins and their presumed function, which is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
267
0
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 410 publications
(274 citation statements)
references
References 45 publications
(52 reference statements)
2
267
0
5
Order By: Relevance
“…First, we showed that [6]-shogaol inhibited melanin synthesis in a concentration-dependent manner without cytotoxicity (1-10 µmol/L) in B16 cells and that the extent of inhibition was comparable between treatment with [6]-shogaol (5 µmol/L) and with kojic acid (200 µmol/L). Second, because tyrosinase is the key enzyme involved in melanogenesis [33,34] , we measured the effect of [6]-shogaol on tyrosinase activity. Interestingly, we found that [6]-shogaol decreased tyrosinase activity in B16 cells, but it did not affect mushroom tyrosinase activity in a cell-free assay system.…”
Section: Discussionmentioning
confidence: 99%
“…First, we showed that [6]-shogaol inhibited melanin synthesis in a concentration-dependent manner without cytotoxicity (1-10 µmol/L) in B16 cells and that the extent of inhibition was comparable between treatment with [6]-shogaol (5 µmol/L) and with kojic acid (200 µmol/L). Second, because tyrosinase is the key enzyme involved in melanogenesis [33,34] , we measured the effect of [6]-shogaol on tyrosinase activity. Interestingly, we found that [6]-shogaol decreased tyrosinase activity in B16 cells, but it did not affect mushroom tyrosinase activity in a cell-free assay system.…”
Section: Discussionmentioning
confidence: 99%
“…Tyrosinase gene family consists of tyrosinase, TRP-1 and TRP-2. They are glycoproteins embedded in the melanosome membrane that share 70-80% nucleotide sequence homology with 30-40% amino acid identity, and share common functional motifs such as epidermal growth factor receptor and copper binding sites (del Marmol and Beermann, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Tyr encodes the enzyme tyrosinase that catalyses the hydroxylation of L-tyrosine to DOPA and the oxidation of DOPA to DOPA-quinone (del Marmol and Beermann, 1996). The role of tyrosinase in two-stage skin carcinogenesis does not appear to involve metabolic activation of DMBA to an ultimate carcinogen, since previous studies demonstrated similar levels of DMBA-DNA adducts in DMBA-treated Car-S and Car-R mice (Perin et al, 1994).…”
Section: Discussionmentioning
confidence: 99%